ANALISIS STRATEGI PEMASARAN LAYANAN CASH MANAGEMENT SYSTEM SEBAGAI PROGRAM BANK SYARIAH DI INDONESIA - Sanjayawati, Hilda; Sendiabsari, Rahma Tiwik (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the marketing strategies of Cash Management System (CMS) services in Islamic banks in Indonesia. CMS is a digital banking innovation that plays an important role in improving the efficiency of financial transactions, particularly for corporate customers. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that CMS marketing strategies are influenced by several key factors, including technological readiness, customer trust, market education, and compliance with Islamic principles. Effective strategies include digital marketing, relationship marketing, and educational approaches based on Islamic values. Trust acts as a mediating variable that significantly affects the decision to adopt CMS services. The study contributes both theoretically and practically to the development of digital-based Islamic banking services.